Formulasi Sediaan Lip Balm Minyak Zaitun Halal dan Uji Kestabilan Fisik - Ningrum, Yuyun Darma Ayu; Azzahra, Nurul Hidayah (Indonesian Journal of Pharmacy and Natural Product, 2022)
Lip Balm is a cosmetic preparation with the main components such as wax, fat and oil from natural or synthesized extracts with the aim of preventing dryness of the lips by increasing lip moisture and protecting the adverse effects of the environment on the lips. Based on the explanation above, the purpose of this study was to formulate lip balm preparations using olive oil and review the results of physical stability tests. Researchers made a modified formulation based on Simplex Lactis Design by using a combination of cera alba and cera flava as the basis of the formulation with a concentration of 16.25% cera alba and Â 8.75% cera flava. Observations were made on olive oil lip balm including pH test, homogeneity test, melting test of the preparation, adhesion test and stability test of the preparation. The results of the analysis showed that olive oil lip balm had a good pH value, homogeneity, melting preparation and adhesion, and was stable in the stability test. ABSTRAKLip Balm merupakan sediaan kosmetik dengan komponen utama seperti lilin, lemak dan minyak dari ekstrak alami atau yang disintesis dengan tujuan untuk mencegah terjadinya kekeringan pada bibir dengan meningkatkan kelembaban bibir dan melindungi pengaruh buruk lingkungan pada bibir. Berdasarkan pemaparan diatas tujuan dari penelitian ini dilakukan untuk memformulasikan sediaan lip balm dengan menggunakan minyak zaitun dan ditinjau hasil uji stabilitas fisiknya. Peneliti melakukan formulasi dengan modifikasi berdasarkan Simplex Lactis Design dengan menggunakan kombinasi cera alba dan cera flava sebagai basis formulasi dengan konsentrasi cera alba 16,25% dan cera flava 8,75% . Pengamatan yang dilakukan pada lip balm minyak zaitun meliputi uji pH, uji homogenitas, uji lebur sediaan, uji daya lekat dan uji stabilitas sediaan. Hasil analisis yang didapatkan menunjukan lip balm minyak zaitun memiliki nilai pH, Homogenitas, lebur sediaan dan daya lekat yang baik, serta stabil dalam uji stabilitas.